Economic evaluation of an expanded caries-preventive program targeting toddlers in high-risk areas in Sweden. (19th May 2019) - Anderson, Maria; Davidson, Thomas; Dahllöf, Göran; Grindefjord, Margaret
Abstract: Objective: To economically evaluate a caries-preventive program "Stop Caries Stockholm" (SCS) where a standard program is supplemented with biannual applications of fluoride varnish in toddlers and compared it with the standard preventive program. Material and methods: Data from the cluster randomized controlled field trial SCS including 3403 children, conducted in multicultural areas with low socioeconomic status was used. The difference in mean caries increment between the examinations; when the toddlers were 1 and 3 years old, was outcome measure of the intervention. The program was evaluated from a societal as well as a dental health care perspective. The incremental cost-effectiveness ratio (ICER) was calculated as the incremental cost for each defs prevented. Results: Average dental health care costs per child at age 3 years were EUR 95.77 for the supplemental intervention and EUR 70.52 for the standard intervention. The ICER was EUR 280.56 from a dental health care perspective and EUR 468.67 and considered high. Conclusions: The supplemental caries intervention program was not found to be cost-effective. The program raised costs without significantly reducing caries development. A better alternative use of the resources is recommended. Trial registration:www.controlled-trials.com (ISRCTN35086887).